2017
DOI: 10.3390/molecules22071049
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sulfamide-Containing Compounds as Selective Carbonic Anhydrase I Inhibitors

Abstract: The development of isoform selective inhibitors of the carbonic anhydrase (CA; EC 4.2.1.1) enzymes represents the key approach for the successful development of druggable small molecules. Herein we report a series of new benzenesulfamide derivatives (-NH-SO2NH2) bearing the 1-benzhydrylpiperazine tail and connected by means of a β-alanyl or nipecotyl spacer. All compounds 6a–l were investigated in vitro for their ability to inhibit the physiological relevant human (h) CA isoforms such as I, II, IV and IX. Mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…The next three papers in the special issue [ 37 , 38 , 39 ] deal with targeting carbonic anhydrases (CAs) from various organisms [ 1 , 2 , 8 , 9 , 10 , 11 , 12 ]. Indeed, these metalloenzymes are potently inhibited by various classes of sulfonamides, many of which show pharmacologic applications as antiglaucoma [ 8 , 10 ], antiobesity [ 13 ], antitumor [ 8 , 9 , 11 , 18 ], or diuretic [ 15 ] drugs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The next three papers in the special issue [ 37 , 38 , 39 ] deal with targeting carbonic anhydrases (CAs) from various organisms [ 1 , 2 , 8 , 9 , 10 , 11 , 12 ]. Indeed, these metalloenzymes are potently inhibited by various classes of sulfonamides, many of which show pharmacologic applications as antiglaucoma [ 8 , 10 ], antiobesity [ 13 ], antitumor [ 8 , 9 , 11 , 18 ], or diuretic [ 15 ] drugs.…”
mentioning
confidence: 99%
“…In the paper by Berrino et al [ 39 ] a new series of benzenesulfamide derivatives (-NH-SO 2 NH 2 ) which incorporate a 1-benzhydrylpiperazine tail, connected to the sulfonamide scaffolf by means of β-alanyl or nipecotyl spacers was reported and investigated for the inhibition of CAs of human (h) origin, such as hCA I, II, IV and IX. Some of these isoforms are established drug targets, but many sulfonamide or sulfamide inhibitors show little selectivity when inhibiting them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An Applied Photophysics stopped-flow instrument was used for assaying the CA catalyzed CO 2 hydration activity ( Khalifah, 1971 ). The method was exactly as described previously ( Berrino et al, 2017 ) except that the inhibitor dilutions were done up to 0.5 nM.…”
Section: Methodsmentioning
confidence: 99%
“…To further explore the molecular determinants responsible for potent and selective inhibition of hCAs by carboxylic acids, here we used the tail approach to design a number of derivatives of the previous CAI hit GV2-20. Indeed, this is a versatile tool to design and optimize hit and lead CAIs possibly improving potency and selectivity [ 49 , 50 ]. Our previous results showed that the symmetric 3,5-dinitrobenzoic acid moiety of GV2-20 binds preferentially the catalytic site, thus becoming the head of the molecular scaffold; accordingly, the tail moiety is expected to bind the external and highly variable region of hCAs [ 51 ] and enhance selectivity inhibition.…”
Section: Introductionmentioning
confidence: 99%